PENGARUH PENERAPAN METODE REWARD DAN PUNISHMENT TERHADAP KEMAMPUAN NUMERASI SISWA KELAS III DI UPT SPF SDN 104205 TEMBUNG - Tessa Trifani Turnip; Elvi Mailani; Putra Afriadi; Syahrial (STKIP Subang, 2026)
This study aimed to examine the effect of implementing the reward and punishment method on the numeracy skills of third-grade students at UPT SPF SDN 104205 Tembung in the 2025/2026 academic year. The study employed a quantitative approach using a pre-experimental method with a one-group pretest-posttest design. The sample consisted of 21 third-grade students. The research instrument was a numeracy skills test that had met the validity and reliability requirements. Data were analyzed using the normality test and the paired-samples t-test. The findings showed that the mean pretest score increased from 59.43 to 78.86 in the posttest, representing an improvement of 19.43 points. The normality test indicated that the data were normally distributed, while the hypothesis test produced a t-value of 13.535 with a significance value of 0.001 (< 0.05), indicating that the null hypothesis was rejected. These findings demonstrate that the implementation of the reward and punishment method has a significant effect on students' numeracy skills. The method not only improves numeracy achievement but also enhances students' motivation, participation, and discipline during the learning process. Therefore, the reward and punishment method can be considered an effective instructional strategy for improving elementary school students' numeracy skills.